2018
DOI: 10.3758/s13415-018-0602-8
|View full text |Cite
|
Sign up to set email alerts
|

Brain mechanisms involved in angry prosody change detection in school-age children and adults, revealed by electrophysiology

Abstract: Voices transmit social signals through speech and/or prosody. Emotional prosody conveys key information about the emotional state of a speaker and is thus a crucial cue that one has to detect in order to develop efficient social communication. Previous studies in adults reported different brain responses to emotional than to neutral prosodic deviancy. The aim of this study was to characterize such specific emotional deviancy effects in school-age children. The mismatch negativity (MMN) and P3a evoked potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 86 publications
2
4
0
Order By: Relevance
“…The double peak pattern observed in this study has previously been reported in a vMMN study in children using simple nonsocial stimuli (Cleary et al, 2013), but also in the auditory domain in response to emotional sounds (Charpentier et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…The double peak pattern observed in this study has previously been reported in a vMMN study in children using simple nonsocial stimuli (Cleary et al, 2013), but also in the auditory domain in response to emotional sounds (Charpentier et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…While adults displayed a typical fronto‐central topography of the MMN, children presented a less frequent pattern with small frontal positivity and posterior negativity. The posterior topography of the MMN reported in children for complex deviancy is not typical, but it has already been reported elsewhere for neutral speech sounds (Charpentier et al., 2018). It could reflect a less mature change‐detection response than the classical response observed in adults, as such posteriorly distributed immature response has also been reported for the N1 component in response to tones (Bruneau, Roux, Guérin, Barthélémy, & Lelord, 1997; Goodin, Squires, Henderson, & Starr, 1978; Pang & Taylor, 2000).…”
Section: Discussionsupporting
confidence: 65%
“…Vowels. Twenty productions of the vowel /a/ were selected from a larger material set, all produced with female voices 1 (Charpentier et al, 2018). All stimuli lasted 400ms and were equalized in RMS amplitude.…”
Section: Stimulimentioning
confidence: 99%